2009
DOI: 10.1111/j.1365-2044.2009.05916.x
|View full text |Cite
|
Sign up to set email alerts
|

Optimal remifentanil dosage for providing excellent intubating conditions when co‐administered with a single standard dose of propofol

Abstract: SummaryThis dose-response study aimed to determine the dose of remifentanil combined with propofol 2.5 mg.kg )1 which provided excellent intubation conditions in 95% of patients. Ninety premedicated female ASA 1 and 2 patients were randomly allocated to five remifentanil dose groups (1, 2, 3, 4 or 5 lg.kg )1 ). Induction of anaesthesia was performed with a blinded dose of remifentanil infused over 60 s simultaneously co-administered with propofol 2.5 mg.kg )1 infused over 45 s. Tracheal intubation was attempte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
2
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 35 publications
1
37
2
1
Order By: Relevance
“…Higher doses of remifentanil (three to 5 μg/kg) provide good intubating conditions when used as a substitute for muscle relaxant [3][4][5][6], but no studies to date have examined its effect on IOP. Increases in IOP are mainly caused by increases in episcleral venous pressure (that is determined by central venous pressure), and blood volume of the eye (that is influenced by cerebral blood flow and volume), or agents that might increase extraocular muscle tone [7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Higher doses of remifentanil (three to 5 μg/kg) provide good intubating conditions when used as a substitute for muscle relaxant [3][4][5][6], but no studies to date have examined its effect on IOP. Increases in IOP are mainly caused by increases in episcleral venous pressure (that is determined by central venous pressure), and blood volume of the eye (that is influenced by cerebral blood flow and volume), or agents that might increase extraocular muscle tone [7].…”
Section: Discussionmentioning
confidence: 99%
“…Rapid-sequence induction of anesthesia using propofol/remifentanil three to 5 μg/kg, without muscle relaxants, also controls the hemodynamic response to laryngoscopy and intubation while providing excellent intubating conditions [3][4][5][6]. However, no study to date has examined the effects of this muscle relaxant-free technique on IOP, which is important when succinylcholine is contraindicated.…”
Section: Introductionmentioning
confidence: 99%
“…9 As expected, we observed a decrease in the ED 95 of remifentanil for providing excellent LMA insertion conditions compared with the IED 95 of remifentanil 4 lgÁkg -1 . 13 This decrease was due to use of a carefully standardized anesthetic induction sequence and consideration of the unique pharmacokinetic and pharmacodynamic attributes of propofol and remifentanil such that LMA insertion occurred at the time when effect-site concentration peaked for both agents. 17,18 In fact, insertion of the LMA constitutes a less noxious stimulus compared with laryngoscopy.…”
Section: Discussionmentioning
confidence: 99%
“…The range of doses of remifentanil for the insertion of the LMA was selected based on the following assumptions: the required dose of remifentanil would be less than twice the dose required to moderate hemodynamic responses to tracheal intubation and more than one-fourth of a 4 lgÁkg -1 dose determined from a recent study in a similar population, 13 and as was previously reported when using alfentanil in combination with propofol. 5 The randomization list was generated by a physician who was not involved in the enrollment of patients into the study.…”
Section: Anesthetic Protocolmentioning
confidence: 99%
“…Kas gevşeticisiz trakeal entübasyon için remifentanil ve propofol öncelikli olarak kullanılmaktadır (6). Alternatif opioid ajanlar alfentanil, fentanil ve sulfentanil, hipnotik ajanlarsa etomidat, tiopental ve sevofuran olarak sıralanmaktadır (7,8).…”
Section: Introductionunclassified